Aktivitas Larvasida Ekstrak Metanol Daun Selasih (Ocimum basilicum) Terhadap Larva Nyamuk Aedes aegypti - Ratnawati, Devi; Manaf, Syalfinaf; Sari, Yanci Novita (Universitas Bengkulu, 2016)
The aim of this research was to investigate the effectivity concentration of basil leafs extract Ocimum basilicum to mortality of Aedes aegypti larvae. The research step were: rearsing larvae, making Ocimum basilicum leaf extract, the phytochemistry screning test of Ocimum basilicum leaf, preliminary test, and effectivity test. The research design was used complete randomized design with 5 treatmant and 1 control, every treatmant used 5 replication and each treatmant used 10 larvae 3th instar Aedes aegypti. Data obtained from examinition of biological effectivity were analysed by using ANOVA and continuously analyzed by multiple range Duncan’s test of a 5% showed just at 700 and 650 mg/L concentration not significant. The result of phytochemistry screning test that leaf extract Ocimum basilicum have contained steroid and flavonoid is toxic on Aedes aegypti larvae and has LC50 605,76 mg/L.